(untitled) (Training and Practice : Journal of Educational Sciences, 2019)
The answers of the questionnaire confuted the presumptions. We believe that the series of tasks and its modernity will have a motivational effect on the students, and that it will assist their orientation in digital world. The main point of the study group is the gaining of experiences, the motivation and assistance in discovered learning. Planning classes by principles of gamification is not an easy task, but worth the work. Students gain real knowledge, due to continuous interest and practice. By collecting points, the students manage the tasks on their own. By choosing the level of difficulty on their own, the students avoid the comparison to others and they follow their own development carefully. We should be more open, and not afraid of new methods. We should get to know today’s children better, so that we can adjust our teaching methods to their needs. We suggest this method, the experience-based teaching and the use of modern developing possibilities, wholeheartedly.